Autoinflammatory Mechanisms in Crystal-Induced Arthritis - Oliviero, Francesca; Bindoli, Sara; Scanu, Anna; Feist, Eugen; Doria, Andrea; Galozzi, Paola; Sfriso, Paolo (Frontiers in Medicine, 2020)
Crystal-induced arthritides have been classified as “type-1 autoinflammatory diseases” for their main features which resemble those of the monogenic autoinflammatory syndromes. They are in fact characterized by spontaneous onset, recurrence of the episodes, self-limitation and resolution, inflammasome activation with huge production of IL-1β and a prevalent involvement of the innate immune system. The term “auto” refers also to the induction of IL-1β gene expression, processing and secretion by IL-1β itself. The concept of autoinflammation in crystal-induced arthritis has been finally reinforced by the efficacy of IL-1 blockade in treating acute and chronic state of those diseases. The aim of this article is to review the autoinflammatory mechanisms in crystal-induced arthritis, considering both clinical and molecular aspects.